GOOD GOVERNANCE EKS-RINTISAN SEKOLAH BERTARAF INTERNASIONAL (RSBI) - Trismanto Trismanto; Yusak Lestari Diyono (FEB UNTAG Semarang, 2014)
The purpose of the research is making a good model of school management (ex-RSBI) having a certain quailty in Semarang City. The population of this research is all managements that is teachers and headmasters of ex-RSBI in Semarang City. Purposive sampling is done (in this research) by taking the samples based on certain criteria and relevant to the research purpose. Approach used is descriptive analytic to know the important and dominant factors in good management of school (ex-RSBI). To know the influences of the good management of school – transparancy of information, school accountability, and other factors found – toward public satisfaction and loyality in Semarang City. The analysis of Partial Least Square (PLS) is used. Data gamed by surveying (by giving quesionnaires to) and interviewing deeply the teachers and headmasters of the selected ex-RSBI in Semarang City. The characteristic of the second year research is only confirmation of school management of ex-RSBI so that the model of good management of ex-RSBI in Semarang city is formed.